Measurement of Ratios of nu(mu) Charged-Current Cross Sections on C, Fe, and Pb to CH at Neutrino Energies 2-20 GeV - Tice, BG (2014)
This work was supported by the Fermi National Accelerator Laboratory under U.S. Department of Energy Contract No. DE-AC02-07CH11359 which included the MINERvA construction project. Construction support also was granted by the United States National Science Foundation under Grant No. PHY-0619727 and by the University of Rochester. Support for participating scientists was provided by NSF and DOE (USA) by CAPES and CNPq (Brazil), by CoNaCyT (Mexico), by CONICYT (Chile), by CONCYTEC, DGI-PUCP and IDI/IGI-UNI (Peru), by Latin American Center for Physics (CLAF), by the Swiss National Science Foundation, and by RAS and the Russian Ministry of Education and Science (Russia). We thank the MINOS Collaboration for use of its near detector data. Finally, we thank the staff of Fermilab for support of the beam line and detector.